2005
DOI: 10.1074/jbc.m506181200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Comparison between Secretory Pathway Ca2+/Mn2+-ATPase (SPCA) 1 and Sarcoplasmic Reticulum Ca2+-ATPase (SERCA) 1 Isoforms by Steady-state and Transient Kinetic Analyses

Abstract: Steady-state and transient kinetic studies were performed to functionally analyze the overall and partial reactions of the Ca 2؉ transport cycle of the human secretory pathway Ca 2؉ /Mn 2؉ -ATPase 1 (SPCA1) isoforms: SPCA1a, SPCA1b, SPCA1c, and SPCA1d (encoded by ATP2C1, the gene defective in Hailey-Hailey disease) upon heterologous expression in mammalian cells. The expression levels of SPCA1 isoforms were 200 -350-fold higher than in control cells except for SPCA1c, whose low expression level appears to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
52
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 43 publications
4
52
0
Order By: Relevance
“…Relative to SERCA1a, the SPCA1 enzymes display remarkably high apparent affinities for cytosolic Ca 2ϩ (K 0.5 ϭ 0.01-0.04 M) in activation of the ATPase and phosphorylation activities and relatively low maximal turnover rates (3). Further investigations showed that these differences are mainly due to a reduction in the rate of the energytransducing E 1 ϳP(Ca) to E 2 -P conformational transition (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to SERCA1a, the SPCA1 enzymes display remarkably high apparent affinities for cytosolic Ca 2ϩ (K 0.5 ϭ 0.01-0.04 M) in activation of the ATPase and phosphorylation activities and relatively low maximal turnover rates (3). Further investigations showed that these differences are mainly due to a reduction in the rate of the energytransducing E 1 ϳP(Ca) to E 2 -P conformational transition (3).…”
mentioning
confidence: 99%
“…SPCA2 colocalizes with Golgispecific markers in human colon epithelial cells (10). For SPCA1, further isoform diversity is brought about by alternative splicing of the ATP2C1 pre-mRNA at its 3Ј end giving rise to three functionally active splice variants (SPCA1a of 919 amino acids, SPCA1b of 939 amino acids, and SPCA1d of 949 amino acids) and one inactive truncated isoform (SPCA1c of 888 amino acids) (3,12). So far, no splice variants have been reported for ATP2C2.…”
mentioning
confidence: 99%
“…P-type pumps share a high degree of sequence, structural and functional similarity, and their varied substrate specificities arise from minor changes in their ionbinding residues. During ion transport, autophosphorylation at an invariant aspartic acid residue in the cytoplasmic domain induces a characteristic conformation change from the E1 state, which has high affinity for the ion, to the E2 state, which has low affinity for the ion (1)(2)(3)(4). Transport through these pumps is limited by the rate of this conformational change (2).…”
mentioning
confidence: 99%
“…During ion transport, autophosphorylation at an invariant aspartic acid residue in the cytoplasmic domain induces a characteristic conformation change from the E1 state, which has high affinity for the ion, to the E2 state, which has low affinity for the ion (1)(2)(3)(4). Transport through these pumps is limited by the rate of this conformational change (2). Devising molecular techniques that can increase ion transport through P-type ATPases will significantly improve our understanding of cellular processes regulated by these pumps and may also contribute to new treatments of diseases related to these processes.…”
mentioning
confidence: 99%
“…Typically, a new steady-state level of fluorescence was established after 2-3 min of superfusion. The catalytic transport cycle of SERCA involves a phosphor-enzyme intermediate, and the phosphorylation and dephosphorylation of the enzyme during Ca 2ϩ transport are markedly enhanced by Mg 2ϩ (16,25,51). Therefore, 1 min before addition of InsP3 and throughout application of InsP3 in the test period, SERCA pump activity was effectively disabled by removal of Mg 2ϩ from the superfusate.…”
Section: Methodsmentioning
confidence: 95%